Identification and distribution of sea cucumber exploited in Lampung, Indonesia - ANA SETYASTUTI; ISMILIANA WIRAWATI; MARINDAH YULIA ISWARI (Biodiversitas Journal of Biological Diversity, 2018)
Setyastuti A, Wirawati I, Iswari MY. 2018. Identification and distribution of sea cucumber exploited in Lampung, Indonesia. Biodiversitas 19: 726-732. Recently approx. 54 species of sea cucumbers were successfully listed that still being exploited from Indonesian waters. However, out of those only 33 species were taxonomically confirmed because the identification of remaining 21 species need to be verified. Inventory on commercial sea cucumber in Bakaheuni water, Lampung was conducted to bridge the gap in fisheries data by addressing the understanding of the diversity of species exploited for trade. Eight commercially important species of sea cucumber were discovered viz. Actinopyga echinites, A. mauritiana, Holothuria (Halodeima) atra, Holothuria (Thymiosycia) impatiens, Holothuria (Acanthotrapeza) coluber, Pearsonothuria graeffei, Stichopus ocellatus and Stichopus vastus during the present study. Two most interesting species namely Actinopyga mauritiana was one of the species that fortuitously confirmed its utilization status as commercial species through this study, and Stichopus ocellatus is newly reported species in Indonesia, not only from fisheries point of view but also taxonomical studies. Hence, the findings of the present study will prove best for the updating of the list of sea cucumber species fished in Indonesia for trade purpose. Till date, we can paraphrase that the number of sea cucumber being involved in a trade is 55 species. It was also concluded that almost 90% of over 650 individuals of sea cucumber found in Bakaheuni waters was observed in the intertidal area, out of which Holothuria atra is the most abundant one. Data presented also revealed that local fishermen are not interested to exploit the low-value species of sea cucumber.